Exponential input-to-state stability of composite stochastic systems - Abedi, Fakhreddin; Leong, Wah June; Chaharborj, Sarkhosh Seddighi (SpringerOpen, 2013)
Sufficient conditions for the exponential input-to-state stability in probability in rth mean and for the almost sure exponential input-to-state stability in probability of a composite stochastic system are established. Illustrating example is provided to validate our results.